Adjustment of college students and high school students who like watching Korean dramas - Elni Yakub; Tri Umari; Munawir Munawir (Indonesian Institute for Counseling, Education and Therapy (IICET), 2023)
Most Korean drama fans are students. Watching Korean dramas also impacts students' attitudes and behavior, including their adjustment to campus life. This research aims to determine the adjustment of students who enjoy watching Korean dramas in terms of emotional maturity, intellectual maturity, social maturity, and responsibility. The study follows a quantitative descriptive research design and was conducted at the Faculty of Teacher Training and Education, Riau University. The sampling technique employed was the snowball sampling method, resulting in a sample size of 102 participants. Data for this research consist of interval data collected through respondents filling out the self-adjustment scale instrument. Descriptive analysis was used to analyze the data. The research findings reveal that students who enjoy watching Korean dramas exhibit medium-level adjustments in three aspects: emotional maturity, intellectual maturity, and responsibility. However, one aspect of adjustment falls into the low category—social maturity. Therefore, students classified in the low social maturity category may benefit from interventions to enhance their social relations maturity on campus.